Implementasi Wisata Ramah Muslim Eco Wisata Mangrove Cuku Nyi-Nyi di Desa Sidodadi Kecamatan Teluk Pandan - Aldo Faturizki; Syamsul Hilal; Ani Ayu Safitri; Dian Ramadhani; Fitri Handayani; Intan Mawarni; Putri Minamas; Rahmat Ikhlas Randi P.S; Repi Dina Cahya R (Lembaga Pengembangan Kinerja Dosen, 2024)
Muslim-friendly tourism is a tourism that is developed by providing facilities needed by Muslim tourists, ranging from facilities for places of worship to worship equipment, such as mukena, sarongs, and prayer mats. Muslim-friendly tourism has been widely developed in various tourist attractions in Indonesia. This research aims to implement Muslim-friendly tourism in Cuku Nyi-Nyi Mangrove Ecotourism. The object of this research is the Cuku Nyi-Nyi Mangrove Ecotourism located in Sidodadi Village, Teluk Pandan District, Pesawaran Regency, Lampung Province. This research method uses descriptive research to develop a systematic, fact-based, and accurate plan about the facts and characteristics of a particular population or region. The results of this study show that the implementation of Muslim-friendly tourism in Cuku Nyi-Nyi Mangrove Ecotourism has been successfully implemented.